Nebulization of model hydrogel nanoparticles to macrophages at the air-liquid interface - Sudduth, Emma R.; Kolewe, Emily L.; Graf, Jodi; Yu, Yinkui; Somma, Joaquina; Fromen, Catherine A. (Frontiers in Chemical Engineering, 2023)
Nanoparticle evaluation within the pulmonary airspace has increasingly important implications for human health, with growing interest from drug delivery, environmental, and toxicology fields. While there have been widespread investigations of nanoparticle physiochemical properties following many routes of administration, nanoparticle behavior at the air-liquid interface (ALI) is less well-characterized. In this work, we fabricate two formulations of poly(ethylene)-glycol diacrylate (PEGDA)-based model nanoparticles to establish an in vitro workflow allowing evaluation of nanoparticle charge effects at the ALI. Both cationic and anionic PEGDA formulations were synthesized with similar hydrodynamic diameters around ~225 nm and low polydispersity, with expected surface charges corresponding with the respective functional co-monomer. We find that both formulations are readily nebulized from an aqueous suspension in a commercial Aeroneb® Lab Nebulizer, but the aqueous delivery solution served to slightly increase the overall hydrodynamic and geometric size of the cationic particle formulation. However, nanoparticle loading at 50 µg/ml of either formulation did not influence the resultant aerosol diameter from the nebulizer. To assess aerosol delivery in vitro, we designed a 3D printed adapter capable of ensuring aerosol delivery to transwell 24-well culture plates. Nanoparticle uptake by macrophages was compared between traditional cell culture techniques and that of ALI-cultured macrophages following aerosol delivery. Cell viability was unaffected by nanoparticle delivery using either method. However, only traditional cell culture methods demonstrated significant uptake that was dependent on the nanoparticle surface charge. Concurrently, ALI culture resulted in lower metabolic activity of macrophages than those in traditional cell culture, leading to lower overall nanoparticle uptake at ALI. Overall, this work demonstrates that base-material similarities between both particle formulations provide an expected consistency in aerosol delivery regardless of the nanoparticle surface charge and provides an important workflow that enables a holistic evaluation of aerosolizable nanoparticles.